LITERATURE STUDY: CHARACTERS OF STUDENTS IN CITIZENSHIP EDUCATION IN PRIMARY SCHOOLS FROM THE PERSPECTIVE OF THE PHILOSOPHY OF PROGRESSIVISM - Nurul Ramadhani; Maemonah; Azka, Ibnu; Baldan Haramain, Fathur (Auladuna: Jurnal Pendidikan Dasar Islam, 2024)
Abstract The progress of a nation is largely determined by strong character, to create a nation that is dignified and respected by other nations. This research aims to describe students' character in citizenship education in SD from a progresivism perspective. The method used was library research, which collected data by understanding and studying theories from various literature related to the research. Data were collected from various sources, such as journal articles and books. The data analysis technique used in this research is the content analysis. The research results explain that the philosophy of progressivism believes that the environment can influence character development. At the same time, citizenship education is a science that pays attention to national character and the character of students in elementary schools. From these two perspectives, the philosophy of progressivism and citizenship education both aim to form students' character in accordance with the progress of the Indonesian nation.